O efeito adicional da microeletrólise percutânea em pacientes com tendinopatia do manguito rotador : um ensaio clínico randomizado - Magalhães, Geraldo Carvalho (2023)
Introduction: Rotator cuff tendinopathy is the main cause of shoulder pain and functional loss in adults in Brazil. It is estimated that its prevalence in the Brazilian population is between 5% and 33%. Studies show that conservative treatment may involve physical exercises and electrotherapy. Percutaneous microelectrolysis (MEP) is a minimally invasive therapeutic method that has been used with good results in tendinopathies, although the evidence about its use alone or associated with physical exercises is still not well defined. Objective: To compare a shoulder-specific exercise program with and without the addition of MEP on shoulder pain and function in people with rotator cuff tendinopathy. Materials and methods: This is a randomized, controlled, parallel, single-blind clinical trial in which forty-two subjects diagnosed with rotator cuff tendinopathy were randomly allocated into 2 groups: experimental group (EG) with 21 subjects and control group (CG) with other 21 subjects. Both underwent a clinical protocol of therapeutic exercises, but only GE received additional treatment with MEP. To evaluate the outcomes of this study, the questionnaire for shoulder function SPADI (Shoulder Pain and Disability Index) and the EN (Numeric Scale) for pain assessment were used, applied before and 8 weeks after the treatment protocol of 6 face-to-face and supervised sessions by professional. All participants were recommended to practice therapeutic exercises at home. Results: Positive changes were observed both in the outcome pain and in function in both groups, with a decrease in the score in the EG for the SPADI (DM= -35.76; CI95%= -47.77 to -23.76; p<0.001) and for the NE (DM= -3.19; CI95%= -4.45 to -1.94; p<0.001), as well as in the CG for the SPADI (DM= -38.26; CI95%= -50.45 to -26.07 ; p<0.001) and MS (DM= -3.99; CI95%= -5.27 to -2.72; p<0.001), however there were no statistically significant differences between groups, both for function (DM= 7.17: CI95%= -7.02 to 21.35; p=0.317) as for pain (DM= 1.23; CI95%= -2.54 to 0.07; p=0.064). Conclusion: The findings of this study do not allow us to state that the addition of MEP to a therapeutic exercise program is more effective than the isolated use of the latter, although both protocols have positively altered pain and function variables.